Legal Education on Consumer Rights: Community Empowerment Efforts in the Face of Unfair Business Practices - Flora, Henny Saida; Sutresna, Iyos; Abdul, Kartini Maharani; Ningrum, Dedah; Firmansyah, Firmansyah (Abdimas Indonesian Journal, 2024)
The objective of this research is to evaluate the efficacy of legal education in enhancing individuals' comprehension of consumer rights and to develop strategies to equip people with the tools to address unfair business practices. In this context, consumer rights encompass a range of aspects that are vital for the protection of individuals engaged in trade and consumption activities. In light of the fact that a considerable proportion of the population remains inadequately informed about their rights, particularly in the context of unfair business practices, the provision of legal education is of paramount importance. This study employs a qualitative methodology to examine individuals' experiences and perspectives on consumer rights, underscoring the significance of legal education in enhancing people's comprehension of consumer rights. Legal education ought to be pursued in a sustainable manner, with the active involvement of diverse stakeholders, including governmental bodies, non-governmental organisations (NGOs), and local communities. To enhance the efficacy of legal education, it is essential to utilise digital technology as a conduit for information dissemination.